PEMIDANAAN TERHADAP PENYANDANG DISABILITAS MENTAL SEBAGAI PELAKU TINDAK PIDANA PENCABULAN (STUDI PUTUSAN PERKARA NOMOR 16/Pid.Sus/2019/Pn.Wsb) - Kadek Januarsa Adi Sudharma; Ayu Meiranda (Jurnal Hukum Saraswati (JHS), 2021)
This study aims to determine the punishment of persons with mental disabilities who commit criminal acts and the criminal responsibility of persons with mental disabilities as perpetrators of criminal acts of obscenity in Decision Number: 16/Pid.Sus/2019/Pn.Wsb at the Wonosobo District Court. This research is a type of normative legal research that is prescriptive. This legal writing uses a law approach and a case approach. The legal materials used in writing this law are primary legal materials in the form of the 1945 Constitution, the Criminal Code (KUHP). Wonosobo District Court Decision NUMBER 16/Pid.Sus/2019/Pn.Wsb, RI Law Number 35 of 2014 concerning Amendments to Indonesian Law Number 23 of 2002 concerning Child Protection, Law Number 8 of 2016 concerning Persons with Disabilities and secondary legal materials in the form of books, journals, reports, and dictionaries relating to the punishment of mental disabilities as perpetrators of sexual abuse. The technique of collecting legal materials used is literature study. Based on the results of research and discussion, people with mental disabilities cannot be held responsible for their actions so that in the Wonosobo District Court Decision Number: 16/Pid.Sus/2019/Pn.Wsb against people with mental disabilities as perpetrators of criminal acts of sexual abuse, the judge acquitted the defendant from all lawsuits. Penelitian ini bertujuan untuk mengetahui Pemidanaan terhadap Penyandang disabilitas mental yang melakukan tindak pidana serta pertanggungjawaban pidana penyandang disabilitas mental sebagai pelaku tindak pidana pencabulan dalamPutusan Nomor: 16/Pid.Sus/2019/Pn.Wsb di Pengadilan Negeri Wonosobo. Penelitian ini termasuk jenis penelitian hukum normatif yang bersifat preskriptif. Penulisan hukum ini menggunakan pendekatan undang-undang dan pendekatan kasus. Bahan hukum yang digunakan dalam penulisan hukum ini adalah bahan hukum primer yang berupaUUD 1945, KUHP.Putusan Pengadilan Negeri Wonosobo NOMOR 16/Pid.Sus/2019/Pn.Wsb, Undang - Undang RI Nomor 35 Tahun 2014 tentang Perubahan atas Undang-undang RI Nomor 23 Tahun 2002 tentang Perlindungan Anak,Undang-undang Nomor 8 Tahun 2016 tentang Penyandang Disabilitas dan bahan hukum sekunder yang berupa buku, jurnal, laporan, dan kamus yang berkaitan dengan pemidanaan disabilitas mental sebagai pelaku tindak pidana pencabulan. Teknik pengumpulan bahan hukum yang dilakukan adalah dengan studi kepustakaan. Berdasarkan hasil penelitian dan pembahasan, penyandang disabilitas mental tidak dapat bertanggungjawab terhadap perbuatannya sehingga dalam Putusan Pengadilan Negeri Wonosobo Nomor: 16/Pid.Sus/2019/Pn.Wsb terhadap penyandang disabilitas mental sebagai pelaku tindak pidana pencabulan hakim membebaskan terdakwa dari segala tuntutan hukum.